Representasi Gaya Hidup Mahasiswa pada Instagram dalam Perspektif Hiperrealitas - Octaria, Deby Febrina; Yenis Alda; Mulyani Istiqomah; Vieronica Varbi Sununianti; Deni Aries Kurniawan; Istiqoma Istiqoma (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to examine how student lifestyles are represented on Instagram and how these representations can be understood through the concept of hyperreality. The research applies a qualitative approach using a literature review method by analyzing relevant scientific articles published within the last ten years. The findings indicate that Instagram is not only used as a communication medium but also as a space for self-representation. Students tend to upload curated content that highlights selected aspects of their lives, often emphasizing positive and visually appealing experiences. This practice reflects a process of constructing identity in the digital space. Through Jean Baudrillard’s perspective, these representations can be seen as forms of simulation that produce simulacra, where representations no longer directly refer to actual reality. As a result, a condition of hyperreality emerges, in which the boundary between reality and representation becomes increasingly blurred. This situation influences how students interpret social life and interact within digital environments. The study highlights the importance of understanding social media not only as a platform for interaction but also as a space where meanings and perceptions of reality are continuously shaped.